Seismic Analysis of High Rise Building Structure Considering Flat and Grid Slab : A Review - Singh, Paritosh; Joshi, Rajesh (International Journal of Scientific Research in Civil Engineering, 2019)
Modern slab systems have shown great potentials in the field of conventional slab casting. Recent advances in the field of RCC Design are related to the use of Flat Slabs and Grid Floors. Flat slabs are versatile elements which are widely adopted in construction providing quick construction, minimum depth, and allowing flexible column grids. In flat slabs, the beams used in conventional slabs are taken away and the slab is made to rest directly over the columns. In case of higher loads, a drop panel or a column head may be provided to reduce the intensity of loads. They are particularly appropriate for areas where tops of partitions need to be sealed to the slab soffit for acoustic or fire reasons. On the other hand, grid floor systems consist of a large number of beams spaced at regular intervals in perpendicular directions, monolithic with slab. The rectangular or square void thus formed in the ceiling is advantageously utilized for works such as providing concealed architectural lighting. Grid floors are generally employed for architectural reasons in case of large rooms such as theatre halls, auditoriums, vestibules, and show rooms of shops where column free space is the main requirement. In this study we are review the past researches and publications describing efficiency of different type of slab over different structures. This paper will help in understanding the potential of different slab types and their utilization in structural analysis and designing.
Keywords: Flat Slabs; Grid Floors; Monolithic & SAP2000.Pro; Cost Analysis; Structure